Enhancing visual art communication for Ar-Rahnu awareness - Wan Mohamed, Nik Rozilaini; Sharif, Ziauddin (2024)
Ar-Rahnu provides a convenient source of funding for those who encounter challenges from traditional financial institutions. Ar-Rahnu is Islamic pawnbroking that allows individuals to obtain loans using their valuables as collateral by adhering to Islamic principles such as the prohibition of usury (riba). Ar-Rahnu is also known as Islamic pawnbroking which is Sharia-compliant financing scheme that allows individuals to obtain loans by pledging their valuable assets as collateral (Azman, Kassim, & Adeyemi, 2018).